Pengaruh Kompos Ela Sagu dengan Mikroorganisme Antagonis Terhadap Kemasaman, P Tersedia dan N-Total Tanah pada Ultisols - Elizabeth Kaya; Arni Buton (JURNAL BUDIDAYA PERTANIAN, 2020)
Agricultural waste, such as sago ‘ela’ or sago extraction waste, can be used as an organic fertilizer to improve the physical, chemical and biological properties of the soil. In addition to organic fertilizer from sago ‘ela’, microorganisms can also be used to increase soil fertility. The purpose of this study was to examine the effect of sago ‘ela’ compost and antagonistic microorganisms in the process of changing acidity (pH and Al-exc), availability of P, and total N in Ultisols soil. The research took place at the Laboratory of Soil, Water, and Plant Analysis, Faculty of Agriculture, Pattimura University, Ambon, in June - September 2016. The experiment was carried out with a completely randomized design (CRD) with a factorial arrangement of 4 x 3, with 3 replications. The treatments of providing sago ‘ela’ compost consisted of: no compost (K0), 15 g/kg of soil (K1), 22, 5 g/kg of soil (K2), 30 g/kg of soil (K3). Inoculum provision of antagonistic microorganisms consisted of: without inoculum (A0), Trichoderma sp inoculum 20 mL (A1), and Azotobacter sp inoculum 20 mL (A2). The experiment used 3 replications. The results showed that soil pH was increased by compost and antagonistic microorganisms. However, the effect of compost does not depend on the presence or absence of antagonistic microorganisms and vice versa. Al-exc concentrations were reduced by compost and microorganisms, but the effect of microorganisms only occurred in the soil without compost and in the treatment of 15 g/kg of soil (K1). Above these compost doses, the effect of microorganisms was not significant. The concentrations of available P and total soil N were increased by compost and microorganisms, and the effect of compost was greater if accompanied by the application of Azotobacter sp. Keywords: acid soil, antagonistic microorganisms, compost, sago‘ela’ ABSTRAK Limbah pertanian, seperti ela sagu atau limbah ekstraksi sagu, dapat digunakan sebagai bahan pupuk organik untuk memperbaiki sifat fisik, kimia dan biologi tanah. Selain pupuk organik dari ela sagu, mikroorganisme juga dapat digunakan untuk meningkatkan kesuburan tanah. Tujuan penelitian ini adalah untuk mengkaji pengaruh pemberian kompos ela sagu dan mikroorganisme antagonis dalam proses perubahan kemasaman (pH dan Al-dd), ketersediaan P, dan N total pada tanah Ultisols. Penelitian berlangsung di Laboratorium Analisis Tanah, Air, dan Tanaman Fakultas Pertanian, Universitas Pattimura Ambon, pada bulan Juni - September 2016. Percobaan dilakukan dengan Rancangan Acak Lengkap dengan pola faktorial 4 × 3, dengan tiga ulangan. Perlakuan pemberian kompos ela sagu terdiri atas: tanpa kompos (K0), 15 g/kg tanah (K1), 22,5 g/kg tanah (K2), 30 g/kg tanah (K3). Pemberian inokulum mikroorganisme antagonis terdiri atas: tanpa inokulum (A0), inokulum Trichoderma sp 20 mL (A1), dan inokulum Azotobacter sp 20 mL (A2), Percobaan menggunakan 3 ulangan. Hasil penelitian menunjukkan bahwa pH tanah ditingkatkan oleh kompos dan mikroorganisme antagonis. Tetapi, pengaruh kompos tidak tergantung pada ada atau tidak adanya mikroorganisme antagonis dan sebaliknya. Kosentrasi Al-dd diturunkan oleh kompos dan mikroorganisme, tetapi pengaruh mikroorganisme hanya terjadi pada tanah yang tidak diberi kompos dan pada perlakuan 15 g/kg tanah (K1). Di atas dosis kompos tersebut pengaruh mikroorganisme tidak nyata. Konsentrasi P tersedia dan N total tanah ditingkatkan oleh kompos dan mikroorganisme, dan pengaruh kompos lebih besar jika disertai pemberian Azotobacter sp. Kata kunci: ‘ela’ sagu, kompos, mikroorganisme antagonis, tanah masam